ATTENDEES TO THE MUSIC EDUCATION DEPARTMENT PERCEPTIONS - Bahar GÜDEK (Fırat University, 2019)
In this resarch, musical perceptions of the attendees to the Music Education Department have been analyzed according to the gender variable and by considering the elements of rythm, melody, harmony and syntax. Musical perception is feeling and comprehending the reality of music by way of senses. That is to say, musical perception is a whole with the dimensions of psychomotor, intuitional and cognitive. Among those dimensions, the perception of the fundamental elements such as rythm, melody and harmony and together with this perception the naming, analysing and interpretation of those, music is definitely cleared up and becomes understandable. This resarch has been applied on coincidentally selected 49 female and 45 male, totally 94 students attending different classes at 19 May University The Fine Art Education Department Music Education Department during the academic year 2011-2012. Providing the attendees with an opportunity to listen twelve musical works in various varieties. Then they have made an assessment in terms of rythm, harmony and melody on those musical works with “Likert Type Scale” based on 5 points. Resarch results indicate a differentiation on musical perceptions of the students building up this working group at 19 May University The Fine Art Education Department Music Education Department according to their gender quality when they listen to; 1.Turkish Folk Music and Turkish Arabesque Music on the element of syntax. 2. Turkish Art Music, Classic Music and Rock Music on the elements of of rythm. 3.Turkish Pop Music on the elements of melody, harmony and syntax. 4. Foreign Rap Music and Turkish Rap Music on the elements of melody.